Mayor Erythropoietic Response after Deferasirox Treatment in a Transfusion-Dependent Anemic Patient with Primary Myelofibrosis. (5th November 2013) - Lisette, Del Corso; Enrico, Balleari; Eleonora, Arboscello; Riccardo, Ghio; Manlio, Mencoboni; Omar, Racchi
Abstract : Primary myelofibrosis (PMF) is a myeloproliferative neoplasm frequently complicated by transfusion dependent anemia. Both anemia and transfusion-dependence are associated with a poor outcome, at least in part because of toxic effects of iron overload (IOL). Iron-chelating therapy (ICT) is increasingly used in order to prevent IOL in this setting. Here, we describe the case of a 73-year-old man affected by PMF and severe transfusion-dependent anemia who experienced a dramatic erythroid response after being treated with deferasirox to prevent IOL.